Exploring Gendered Understandings of Peace in Delta State, Nigeria - Ceren Bulduk; Joy Onyesoh; Mimidoo Achakpa (Revue Internationale de Politique de Développement)
In this chapter we draw a picture of alternative visions of peace from the standpoint of individuals affected by violent conflict and engaged in peacebuilding in Delta State, Nigeria. Drawing on interviews conducted with NGOs, a community group, and vigilantes, we identify multiple and sometimes contradictory meanings. We discuss these against theorisations of peace in the academic literature and find resonances that allow us to bring community meanings of peace into conversation with the literature. From our interviews, we identify and discuss an understanding of positive peace that requires economic development. We also identify a vision of harmonious living that involves overcoming negative emotions, and draw on feminist literature to connect this vision to the concepts of maternal thinking and building relations of care. Finally, we identify a commitment to peace as inclusive of women, yet note that the extent and form of inclusion is contested among different actors. Assessing these understandings of peace through a gender lens, we argue that gender logics inform these multiple meanings.